STATE INFORMATION POLICY OF UKRAINE: STRATEGIC GUIDELINES AND MAIN TASKS - MAKIEIEV, dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article provides a comprehensive analysis of Ukraine’s state information policy in the context of digital transformation, socio-political changes, and the full-scale invasion of Ukraine by the Russian Federation that began on February 24, 2022. The focus is placed on the transformation of the role of information policy—from a tool for the development of an information society to one of the key mechanisms for ensuring national security, societal unity, and the information sovereignty of the state. It is defined that the state information policy of Ukraine represents a system of principles, objectives, tasks, and measures aimed at regulating the information sphere, ensuring information security, freedom of speech, access to information, and the protection of national interests in the digital environment. The main directions of the state information policy are highlighted, including: countering disinformation and hybrid threats, supporting independent media, advancing digital technologies, expanding e-governance, creating a unified information space, and promoting the Ukrainian narrative at the international level. Special attention is given to the issues of information security, legal regulation of digital processes, development of media literacy among the population, and preservation of cultural identity through mass media. The article substantiates the need for a systematic and coordinated approach to the implementation of information policy with the involvement of the state, civil society, the business sector, and international partners. It is emphasized that the mass communication system plays an important role in the implementation of state information policy, shaping public consciousness, informing about the activities of state bodies, and promoting political, economic, and cultural values. The article concludes that an effective state information policy is an essential component of the country's modernization, the formation of an open democratic society, and resilience to modern information and communication threats.
Keywords: state information policy; information policy; digital transformation; national security; disinformation; information security; mass media; media literacy; information sovereignty